Pelo muito amor que lhe tenho: a família, as vivências afetivas e as mestiçagens na Comarca do Rio das Velhas (1716-1780) - Fabricio Vinhas Manini (2013)
This research aims to analysis, even starting, the formation of emotional bonds in the intimacy of the family of Rio das Velhas County between 1716-1780. The intention is not to analyze the nuclear family, theme already widely researched by historiography, much less the patriarchal family, but understand the affective experiences present in the more intimate setting of the family as the affection and care for those who are near. These relationships, despite the common idea for the family we have today, were new in the eighteenth century. Until then the affection was not indispensable part of that universe closer. Moreover, these relations were not studied by historiography from an empathetic approach to the eighteenth century. Therefore, the need to think about how they contributed to the formation of families, and sociability for shaping the mestizo cultural universe of Rio das Velhas County in the eighteenth century.